Relacje agencji dotyczące kapitału w spółkach giełdowych - Szapiel, Jolanta (Principal - Agent Relations Between Shareholders and Managers in Stock Market Companies, 2005)
According to the agency theory the incentive and appropriate supervision of them contribute to the limitation of interests’ conflicts between shareholders and managers of a company. The purpose of this paper is to answer to what extent the main theses of the agency theory can be positively verified in stock market companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 58-73